Synchronous Disease Kinetics in a Murine Model for Enterohemorrhagic E. coli Infection Using Food-Borne Inoculation - Flowers, Laurice J.; Bou Ghanem, Elsa N.; Leong, John M. (Frontiers in Cellular and Infection Microbiology, 2016)
Upon colonization of the intestinal epithelium, the attaching and effacing (AE) pathogen Enterohemorrhagic Escherichia coli (EHEC) effaces microvilli and forms pedestal-like structures beneath the adherent bacterium. The production of one of its virulence factors, the phage-encoded Shiga toxin (Stx) results in systemic disease, including the development of renal failure. Although EHEC does not productively infect conventional mice, EHEC infection can be modeled in mice utilizing a derivative of the natural murine AE pathogen Citrobacter rodentium (CR). Gavage of mice with CR(ΦStx2dact), a C. rodentium lysogenized by a phage encoding an Stx variant with high potency in mice, features AE lesion formation on intestinal epithelium and Stx-mediated systemic disease, including renal damage. This model is somewhat limited by mouse-to-mouse variation in the course of disease, with the time to severe morbidity (and required euthanasia) varying by as many as 5 days, a feature that limits pathological analysis at defined stages of disease. In the current study, we altered and optimized the preparation, dose, and mode of delivery of CR(ΦStx2dact), using food-borne route of infection to generate highly synchronous disease model. We found that food-borne inoculation of as few as 3 × 104 CR(ΦStx2dact) resulted in productive colonization and severe systemic disease. Upon inoculation of 1 × 108 bacteria, the majority of infected animals suffered weight loss beginning 5 days post-infection and all required euthanasia on day 6 or 7. This enhanced murine model for EHEC infection should facilitate characterization of the pathology associated with specific phases of Stx-mediated disease.